2021
DOI: 10.3390/antibiotics10050487
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Isavuconazole: Serum Concentration Variability and Success Rates for Reaching Target in Comparison with Voriconazole

Abstract: Isavuconazole (ISZ) is used in the treatment of aspergillosis and mucormycosis. The purpose of this study was to evaluate the therapeutic drug monitoring (TDM) of ISZ samples from a clinical setting performed at Statens Serum Institut. Materials/methods: Isavuconazole serum concentrations were determined by fluorescent detection on a UHPLC. Serum-ISZ (s-ISZ) results were included and compared to those of serum-voriconazole (s-VRZ) in a 33 month period from March 2017. Clinical data were obtained for patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
4
14
1
Order By: Relevance
“…Indeed, our data support this contention, even if TDM could represent a helpful tool in some specific cases. This is in agreement with the recent findings of a retrospective comparative study of TDM of isavuconazole (n = 273 samples from 35 patients) vs. voriconazole (n = 1424 samples from 283 patients) from Denmark [30], which confirmed that isavuconazole is much easier to target compared to voriconazole and concluded that the role of TDM for isavuconazole is not so compelling.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, our data support this contention, even if TDM could represent a helpful tool in some specific cases. This is in agreement with the recent findings of a retrospective comparative study of TDM of isavuconazole (n = 273 samples from 35 patients) vs. voriconazole (n = 1424 samples from 283 patients) from Denmark [30], which confirmed that isavuconazole is much easier to target compared to voriconazole and concluded that the role of TDM for isavuconazole is not so compelling.…”
Section: Discussionsupporting
confidence: 91%
“…The median CL estimate (1.52 L/h) was somewhat lower than that reported in clinical trials (2.2-2.5 L/h) [26,27] and consistently lower than that observed in SOT patients (4.28 L/h). The pharmacokinetic model was reliable in predicting observed concentrations (with good precision and R 2 and low bias), and the interindividual variability on CL (64%) was in line with that reported by previous analysis (43-63%) [30].…”
Section: Discussionsupporting
confidence: 85%
“…The inter- and intra-individual CVs for ISA Cmin of 41.5 and 30.7% that we found shows that the ISA Cmin were variable, especially between patients. Such a finding is in agreement with those of several recent real-life studies that reported inter-individual CVs ranging from 36.6 to 61.5% [ 8 , 9 , 22 , 23 ]. Similarly, the intra-individual CV of 30.7% that we found is similar to the intra-individual CVs previously reported, ranging from 28.2 to 43.4% [ 9 , 10 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…We identified a total of 8 articles on isavuconazole TDM in various patient populations, which included overall data from 368 patients. The majority of included patients had hematological malignancy or were solid organ or hematopoietic stem cell transplant recipients, and a total of 1689 samples were taken for measurements of TDM ( Table 4 ) [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Therapeutic Drug Monitoring (Tdm) Of Isavuconazolementioning
confidence: 99%
“…The majority of patients had isavuconazole levels within what was considered a therapeutic range. The blood levels in patients with adverse events attributable to isavuconazole were similar to those without side effects [ 80 ].…”
Section: Therapeutic Drug Monitoring (Tdm) Of Isavuconazolementioning
confidence: 99%